Early warning system for pastoral herders to reduce disaster risk by using a mobile SMS service - Balt, Suvdantsetseg, author; Oba, Akihiro, author; Wanglin, Yan, author; Myagmarsuren, Altanbagana, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Herders in Mongolia are directly affected by climate change impact more than urban residents. This research project is developing an early warning system to prevent disaster risk by using mobile SMS services based on the partnership between a scientific research group, local policy makers, industrial technology developers and support of pastoral communities. The mobile message based forecasting system has included common weather information, forage information and other local requested information and been delivered in current time since August 2013 in a case study in Biger soum of Gobi-Altai province, Mongolia. After the system had been implemented 98% of participants agreed they had improved knowledge about adaptation to dzuds, understood the importance of information access, found it was manageable for their daily job and believed it would help reduce impacts of climate disasters.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: information delivery; SMS; dzud risk management; adaptation